2018
DOI: 10.1002/chem.201706089
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of an Aluminium/Phosphorus Frustrated Lewis Pair (FLP) with α,β‐Unsaturated Carbonyl Compounds: FLPs as Efficient Two‐Electron Reductants with the Formation of Enolates, a cis‐Enediolate, and an Allene

Abstract: The Al/P-based frustrated Lewis pair (FLP) Mes P-C(AltBu) =C(H)Ph (1; Mes=mesityl) reacted as an efficient two-electron reductant with benzil to afford a cis-enediolate that was coordinated to the FLP through P-O and Al-O bonds and the formation of a seven-membered heterocycle (2). The phosphorus atom is oxidised from +III to +V. Similar heterocycles (3 a to 3 f) were formed if 1 was treated with various enones (acrolein, acrylate, acrylamide). The resulting enolates are bound to the FLP through P-C and Al-O b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 86 publications
3
24
0
Order By: Relevance
“…We assumed that FLPs 1 and 2 , which have two mesityl groups attached to P, are not able to show similar reactions, because in that case the migration of a bulky mesityl group by cleavage of a P−C bond is required. The previously reported reaction of the t Bu 2 Al/P FLP 1 with cyclopropenone at room temperature resulted selectively in the formation of the cyclic addition product 13 , in which the CO group is bonded to the FLP backbone through Al−O and P−C bonds with an intact C 3 ring (Scheme ) . We did not detect an intermediate and did not recognize the slow secondary reaction discussed below.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…We assumed that FLPs 1 and 2 , which have two mesityl groups attached to P, are not able to show similar reactions, because in that case the migration of a bulky mesityl group by cleavage of a P−C bond is required. The previously reported reaction of the t Bu 2 Al/P FLP 1 with cyclopropenone at room temperature resulted selectively in the formation of the cyclic addition product 13 , in which the CO group is bonded to the FLP backbone through Al−O and P−C bonds with an intact C 3 ring (Scheme ) . We did not detect an intermediate and did not recognize the slow secondary reaction discussed below.…”
Section: Resultsmentioning
confidence: 56%
“…At 200 K the 31 P NMR resonance is shifted to 25.6 ppm ( 3 J HP =38.9 Hz) and may indicate that the equilibrium is on the side of the heterocyclic compound 15 . A chemical shift of δ ( 31 P)=21.7 ppm and relatively broad resonances in the NMR spectra at room temperature may confirm a similar equilibrium for the di( tert ‐butyl) compound 13 in solution.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Usually the O or N atoms of substrates (carbonyl compounds, imines) approach the Lewis acidic Al atoms of the FLPs or ALPs as the initiating step of the respective transformation. By the interaction with the metal atom the polarity of the C=O or C=N bonds and the electrophilicity of the C atoms increase and facilitate the nucleophilic attack of the Lewis basic ALP or FLP centers at this position by ring closure [7,8] or by initiating another secondary reaction such as an insertion into a M-C bond [12,13,16]. Azides with a homonuclear N 3 group react with Al/P-based FLPs by coordination of the terminal N atom to the Lewis acidic and basic atoms (see Introduction).…”
Section: Resultsmentioning
confidence: 99%
“…These highly promising materials are considered as attractive alternatives or complements for transition metal catalysts. The majority of FLPs is based on systems with B and P atoms as Lewis acids and Lewis bases [1][2][3][4], but it has recently been shown that Al/P based systems are also highly efficient in various transformations [5][6][7][8][9][10]. Al atoms possess an inherently high Lewis acidity, which makes an activation by electron-withdrawing substituents, as required in B based systems, unnecessary.…”
Section: Introductionmentioning
confidence: 99%